Recanalisation therapy in patients with acute ischaemic stroke caused by large artery occlusion: choice of therapeutic strategy according to underlying aetiological mechanism?. Issue 4 (1st August 2017) - Tian, Chenglin; Cao, Xiangyu; Wang, Jun
Abstract : Various mechanisms underlie causative large artery occlusion (LAO) in patients with acute ischaemic stroke. Cardioembolic and atherosclerotic occlusions are the two most common types. The pathophysiological changes and responses to mechanical thrombectomy (MT) and antithrombotic treatments including thrombolysis, antiplatelet and anticoagulation therapy may vary among patients with different aetiological mechanisms of occlusion. Atherosclerotic occlusion is inclined to have relatively abundant collaterals and larger area of penumbra, hence a relatively wider time window for reperfusion therapy, while poor response to medical thrombolysis and MT. Severe residual stenosis and reocclusion occurred frequently after MT in atherosclerotic LAO. Angioplasty and stenting as rescue or the first-line therapy and more intensified antiplatelet therapy beyond related recommendations in the current guidelines are sometimes used in managing acute causative LAO because of poor recanalisation after recommended standard thrombolysis or MT therapy, which are usually based on individual experience. Standard protocol to establish emergent aetiological diagnosis of causative LAO and individualised aetiology-specific treatment strategy is needed.